Homodinuclear Complexes of [Cu(dppf)]+ or [Ru(bpy)2]2+ with 1,4‐Bis(camphorquinoneimino)benzene (bcqb) as a Redox‐Active Bridging Ligand - Filippou, Vasileios; Bubrin, Martina; Fiedler, Jan; Kaim, Wolfgang (European journal of inorganic chemistry, 2021)
The product μ‐bcqb from the reaction between p‐phenylenediamine and two equivalents of camphorquinone has been used as a potentially conjugated molecular bridge between two complex fragments [Cu(dppf)]+, dppf=1,1‘‐bis(diphenylphosphino)ferrocene, to yield 12+, and between two [Ru(bpy)2]2+ moieties, resulting in 24+. The molecular structure of 1(BF4)2 shows an intramolecular Cu−Cu distance of 8.04 Å and a torsionally twisted conformation of the bridge, while cyclic voltammetry, EPR, IR and UV‐vis‐NIR spectroelectrochemistry reveal two closely spaced one‐electron reductions and a ferrocene‐based two‐electron oxidation. Compound 2(PF6)4 exhibits at least three one‐electron reduction waves and one 2e‐oxidation, the former attributed to μ‐bcqb and the latter assigned to metal‐based processes showing no evidence for a Ru−Ru mixed‐valent intermediate. However, intra‐ligand based mixed valency with intense LLIVCT absorptions in the near infrared was observed for the metal coordinated μ‐bcqb.− and μ‐bcqb.3− bridges. The two examples 1n+ and 2n+ illustrate that a combination of physical methods is advantageous to analyze and define the correct electronic structures in complexes involving several metal centers and noninnocent ligand components. Electron transfer was analyzed for molecular systems consisting of a p‐phenylene center, bridging two redox‐active camphorquinoneimino groups which chelate π acceptor‐capped electron‐rich metals CuI or RuII. Intramolecular interaction involving the metal‐supported α‐iminocarbonyl units produces localized mixed‐valent intermediates with intense near infrared absorption.